Potential for HPV vaccination and primary HPV screening to reduce cervical cancer disparities: Example from New Zealand. Issue 42 (8th October 2018) - Smith, Megan A.; Hall, Michaela; Lew, Jie-Bin; Canfell, Karen
Highlights: Cervical cancer rates are higher in Māori vs other women in New Zealand. Both HPV vaccination and HPV screening are predicted to reduce this disparity. Increased vaccine and screening coverage could further reduce but may not close gap. Multiple approaches will be required, including beyond vaccination and screening. These potentially include access to cervical cancer treatment, and tobacco control. Abstract: Background: Cervical cancer rates are over twice as high, and screening coverage is lower, in Māori women compared to other women in New Zealand, whereas uptake of HPV vaccine is higher in Maori females. We aimed to assess the impact of HPV vaccination and the proposed transition to 5-yearly primary HPV screening in Māori and other women in New Zealand, at current participation levels; and additionally to investigate which improvements to participation in Māori females (in vaccination, screening, or surveillance for screening-defined higher-risk women) would have the greatest impact on cervical cancer incidence/mortality. Methods: An established model of HPV vaccination and cervical screening in New Zealand was adapted to fit observed ethnicity-specific data. Ethnicity-specific models were used to estimate the long-term impact of vaccination and screening (vaccination coverage 63% vs 47%; five-year screening coverage 68% vs 81% in Maori vs European/Other women, respectively). Results: Shifting from cytology to HPV-based screening is predicted to reduce cervical cancer incidence by 17% (14%) in Maori (European/Other) women, respectively. The corresponding reductions due to vaccination and HPV-based screening combined were 58% (44%), but at current participation levels long-term incidence would remain almost twice as high in Māori women (6.1/100, 000 compared to 3.1/100, 00 in European/Other women). Among strategies we examined, the greatest impact came from high vaccine coverage and achieving higher attendance by Māori women under surveillance for screen-detected abnormalities. Conclusion: Relative reductions in cervical cancer due to vaccination and HPV-based screening are predicted to be greater in Maori than in European/Other women. While these interventions have the potential to substantially reduce between-group differences, cervical cancer incidence would remain higher in Maori women. These findings highlight the importance of multiple approaches and the potential influence of factors beyond HPV prevention.